PELAKSANAAN PROGRAM REHABILITASI BAGI KORBAN PENYALAHGUNAAN NARKOTIKA DI LEMABAGA PEMASYARAKATAN KELAS II A PEKANBARU - Irawan, Andi; Deliana, Evi; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
According to Article 54 of Law Number 35 Year 2009 on Narcotics said that drug addicts and drug abuse victims must undergo rehabilitation. However, in its implementation in Class II A Pekanbaru, rehabilitation is only carried out by inmates who undergo a judge's verdict. The aim of this thesis are: First, the implementation of rehabilitation programs for victims of abuse of narcotics in Penitentiary Class II A Pekanbaru, Second, Barriers experienced in the implementation of the rehabilitation program in Lemabaga Penitentiary Class II A Pekanbaru, Third, efforts made in overcoming obstacles in the implementation Rehabilitation program at the Class II A Penitentiary Pekanbaru.This type of research can be classified into types of empirical juridical or sociological research, because in this study the authors directly carrying out research at the site under consideration in order to provide a complete and clear picture of the issues examined. This research was conducted at the Penitentiary Class II A Pekanbaru, while the sample population is a whole with regard to the problems examined, the source of the data used primary data, secondary data and data tertiary, data collection techniques in this study with the observation interviews, questionnaire and Literature study.From the results of research problems there are three main things that can be concluded. First, the implementation of the rehabilitation program in Class II A Pekanbaru Prison has been done well and some have not been implemented. Second, barriers encountered in the implementation of rehabilitation in Penitentiary Class II A Pekanbaru, namely, human resources, facilities, time constraints, budget, and rehabilitation clients. Third, efforts made in the face of obstacles in the implementation of rehabilitation in Penitentiary Class II A Pekanbaru, namely: improving human resources, add infrastructure, maximizing time, give strict punishment. Suggestions writer, first, the Government needs to provide assistance to meet the needs of implementing rehabilitation programs so that infrastructure development is met, both, quality and quantity of personnel need to be supported in accordance with the field, third, Need special attention from the relevant agencies (NGOs, BNN, RS, etc).Keywords: Implementation-Rehabilitation-Victim of Narcotics Abuse